Lithologic-facies and paleogeographic features of Mid-Upper Jurassic oil-gas bearing sediments in Nurolsk depression (Western Siberia); IOP Conference Series: Earth and Environmental Science; Vol. 27 : Problems of Geology and Subsurface Development - Rychkova I. V. Irina Vladimirovna; Shaminova M. I. Marina Ivanovna; Sterzhanova V.; Baranova A. V. Anastasia Viktorovna (Ore Deposits. Current Prospecting and Exploration Methods, 2015)
Title screen